Epidemiological characteristics of Acute Flaccid Paralysis cases, Al Najaf Al Ashraf Province, Iraq, 2023-2024 - Y. Khudhair, Abdulhadi; A. Farman, Hassan (Journal of Neonatal Surgery, 2025)
The World Health Organization (WHO) defined an Acute Flaccid Paralysis (AFP) case “as a child presenting with sudden onset of floppy paralysis or muscle weakness due to any cause, or any person of any age with paralytic illness if poliomyelitis is suspected by a clinician”. The study aims to describe epidemiological characteristics of Acute Flaccid Paralysis cases. This study follows a retrospective descriptive design and was implemented in Najaf province; the period of study was from 1 January, 2023 to 31 of December of 2024. The data was collected and reviewed from the patient’s files and surveillance records of all AFP cases. Demographic data include Age, Gender, Residency, vaccination status. Cumulatively, 77 AFP cases were reported to the Najaf between January 2023 and December 2024. Of all cases, 42 (54.5%) were of patients in ages of less than 5 years, and 45 (55.8%) were male. 43 (55.8%) of cases in urban and for Vaccination status 72 (93.5%) were vaccinated. The data indicate that the most commonly affected sites are the lower limbs, with 79.2% of cases involving the left leg and 76.6% involving the right leg. The analysis of risk factors for Acute Flaccid Paralysis (AFP) in Najaf suggests that sex (OR = 1.122, p = 0.694) and residence (OR = 0.893, p = 0.085) are not significantly associated with AFP risk. However, vaccination status (OR = 0.110, p = 0.024) shows a statistically significant protective effect.